Adsorption of Molecular Gases on Silver/Carbon Nanotube Composites at Low Temperatures and Low Pressures - M. Barberio; P. Barone; F. Stranges; R. A. Romano; F. Xu; A. Bonanno (Journal of Chemistry)
We present an experimental study adsorption of molecular gases (N2, H2, O2, CH4, C2H4, and C2H6) on multiwalled carbon nanotubes (MWCNTs) and MWCNT doped with Ag at low temperatures (35 K) and pressures (10−6 Torr) using the temperature programmed desorption technique. Our results show that the desorption kinetics is of the first order; furthermore comparative measurements indicate that Ag/MWCNTs have an adsorption capacity higher than that of a pure sample suggesting that these composites are good candidates as gas cryosorbers for applications in cryopumps or sensor of latest generation.